2020
DOI: 10.1371/journal.pcbi.1008444
|View full text |Cite
|
Sign up to set email alerts
|

BioAFMviewer: An interactive interface for simulated AFM scanning of biomolecular structures and dynamics

Abstract: We provide a stand-alone software, the BioAFMviewer, which transforms biomolecular structures into the graphical representation corresponding to the outcome of atomic force microscopy (AFM) experiments. The AFM graphics is obtained by performing simulated scanning over the molecular structure encoded in the corresponding PDB file. A versatile molecular viewer integrates the visualization of PDB structures and control over their orientation, while synchronized simulated scanning with variable spatial resolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 28 publications
2
76
0
Order By: Relevance
“…A detailed explanation of the simulated AFM scanning method and on general BioAFMviewer applications is provided in our previous report. 15…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A detailed explanation of the simulated AFM scanning method and on general BioAFMviewer applications is provided in our previous report. 15…”
Section: Resultsmentioning
confidence: 99%
“…We have previously demonstrated that manual search can efficiently reveal atomic protein structures from experimental hs-AFM images. 15 On the other hand, the initial orientation may correspond to a candidate fit obtained from global search. In both situations, the Quick Fit function can be used to obtain a further refinement of structure fitting.…”
Section: Local Search -Quick Fit Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assembled hexagonal model satisfied a lattice constant of 17.5 nm. Simulated scanning was performed using the BioAFMviewer software 38 , with a tip that had a probe sphere radius of 1.5 nm and a cone half angle of 10°. The computed AFM graphics was subjected to a Gaussian blur to emulate the averaged experimental AFM images.…”
Section: Methodsmentioning
confidence: 99%
“…The collision-detection method is available as a tool “afmize” ( http://doi.org/10.5281/zenode.3362044 ). The BioAFMviewer, which provides the pseudo-AFM image via a similar method, is also available ( Amyot and Flechsig, 2020 ).…”
Section: Methodsmentioning
confidence: 99%